The social mechanics of good music: a description of dance clubs among the Anlo Ewe-speaking people of Ghana - Ladzekpo, Kobla (International Library of African Music, 1971)
Among the Ewe-speaking people of southeastern Ghana, southern Togoland and southern Dahomey, there are different kinds of music. We have narrative songs, war songs, cradle songs, dirges, play songs, and even chorales (which are foreign to our culture). Along with these one can find different types of cult music belonging to the local rites of worship of the gods, and court music. In African societies, music incorporates dance; therefore music in this paper refers to the drumming, singing, and dancing of the dance clubs
Keywords: Music; Ethnomusicology; Anlo (African people); Societies; Dance; Ghana; Social Life; Social Customs; African Music